2013
DOI: 10.1021/jm400404v
|View full text |Cite
|
Sign up to set email alerts
|

CROSS: An Efficient Workflow for Reaction-Driven Rescaffolding and Side-Chain Optimization Using Robust Chemical Reactions and Available Reagents

Abstract: A novel procedure (CROSS: Computational Rescaffolding and Optimization using Synthetic Schemes) for in silico rescaffolding and side-chain optimization is reported with explicit consideration of the route of synthesis and availability of compatible chemical reagents. We have defined a set of retrosynthetic disconnections representing robust reactions, amenable for combinatorial chemistry. This rule set is used to generate virtual fragment databases from available reagents. Each reactive center is annotated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Evers et al from the Sanofi‐Aventis company reported the CROSS method for either rescaffolding or the optimization of compounds using explicit handling of organic reactions . The CROSS approach relies on the BROOD software to quickly identify pre‐processed fragments that could replace an undesirable core by using “exit vectors” and 3D‐shape analysis .…”
Section: Alternative Approaches For In Silico H2l Optimizationmentioning
confidence: 99%
“…Evers et al from the Sanofi‐Aventis company reported the CROSS method for either rescaffolding or the optimization of compounds using explicit handling of organic reactions . The CROSS approach relies on the BROOD software to quickly identify pre‐processed fragments that could replace an undesirable core by using “exit vectors” and 3D‐shape analysis .…”
Section: Alternative Approaches For In Silico H2l Optimizationmentioning
confidence: 99%
“…In this collection, 58 medicinal chemistry-relevant chemical reactions commonly used during the H2L optimization stage in the pharmaceutical industry have been encoded in the machine-readable SMARTS format. These reactions have been implemented in several approaches including DOGS ( 25 ), CROSS ( 26 ), PINGUI/SCUBIDOO ( 27 , 28 ), AutoCouple ( 29 ), NAOMINEXT ( 30 ), CHIPMUNK ( 31 ), SwissDrugDesign ( 32 ), AutoGrow4 ( 33 ), OpenChemLib ( 34 ) and eXplore ( 35 ). We also implemented this collection of reactions into our integrated drug design strategy called diversity-oriented target-focused synthesis (DOTS, ( 36 )).…”
Section: Introductionmentioning
confidence: 99%
“…To alleviate this problem, several research groups have proposed the use of chemical reaction protocols to guide virtual compound synthesis. Consequently, in recent years, collections of reactions and reactions types have been systematically mined from the chemical literature and, attempts to classify them into reaction types and organize them have been reported. Research efforts to exploit such reaction sets to define large virtual libraries of theoretically feasible chemical structures or exploit them for de novo design purposes and (re)­scaffold-hopping are ongoing.…”
Section: Introductionmentioning
confidence: 99%